Vaccination of Gilthead Seabream After Continuous Xenoestrogen Oral Exposure Enhances the Gut Endobolome and Immune Status via GPER1 - Castejón, Pablo; Cabas, Isabel; Gómez, Victoria; Chaves-Pozo, Elena; Cerezo-Ortega, Isabel; Moriñigo, Miguel Ángel; Martínez-Manzanares, Eduardo; Galindo-Villegas, Jorge; García-Ayala, Alfonsa (Frontiers in Immunology, 2021)
In fish culture settings, the exogenous input of steroids is a matter of concern. Recently, we unveiled that in the gilthead seabream (Sparus aurata), the G-protein-coupled estrogen receptor agonist G-1 (G1) and the endocrine disruptor 17α-ethinylestradiol (EE2) are potent modulators in polyreactive antibodies production. However, the integral role of the microbiota upon immunity and antibody processing in response to the effect of EE2 remains largely unexplored. Here, juvenile seabreams continuously exposed for 84 days to oral G1 or EE2 at a fixed dose of 5 g/g of food were i.p. vaccinated on day 42 with the model antigen keyhole limpet hemocyanin (KLH). A critical panel of systemic and mucosal immune markers, serum vitellogenin, humoral enzymatic, and bacteriolytic activities were recorded and correlated with gut bacterial metagenomic analysis one-day post priming (dpp). Besides, 15 dpp animals received a boost to investigate the systemic- and mucosal-specific anti-KLH titers by the end of the trial. On day 43, EE2 but not G1 induced a significant shift in the serum vitellogenin level of naïve fish. Simultaneously, significant changes in some immune enzymatic activities in the serum, and gut mucus of the EE2 treated group were recorded. In comparison, priming immunization resulted in an attenuated profile in the same group. The gut genes qPCR analysis exhibited a related pattern only emphasized by the significant shift on the EE2 group il1b expression. The gut bacterial microbiome status undergoes 16S rRNA dynamic changes in alpha diversity indices, only with the exposure to dietary G1, supporting functional alterations on cellular processes, signaling, and lipid metabolism. By the same token, the immunization elevates the relative abundance of Fusobacteria only in the control group, while depleted it in both the treated groups and remarkably promoted changes in the bacterial class and the estrogen-associated genera Novosphingobium. Furthermore, systemic and mucosal KLH-specific IgM and IgT titers in the vaccinated fish showed average values 84 days post-estrogenic oral administration. In summary, our results highlight the intrinsic relationship among estrogens, their associated receptors, and vaccination in the ubiquitous fish immune regulation and the subtle but significant crosstalk with the gut endobolome.